Molecular and morphological approaches redefine the limits among polymorphic species in the Neotropical longhorn beetle genus, Myzomorphus Sallé (Coleoptera: Cerambycidae: Prioninae) - Souza, Diego De S.; Sepúlveda, Tatiana A.; Monné, Miguel A.; Marinoni, Luciane; Monné, Marcela L. (Zootaxa, 2023)
Myzomorphus Sallé is a charismatic genus of prionine longhorn beetles (Cerambycidae) composed of nine species. Myzomorphus species are found from Costa Rica to southern Brazil, but only two species have wide distributions across this range: M. scutellatus Sallé from Costa Rica to northern Brazil, and M. quadripunctatus (Gray) from Colombia to southern Brazil. These species are highly polymorphic and their limits are difficult to determine due to their strong morphological similarities––males are only distinguishable by subtle size variations and females by color patterns. Here, we used mitochondrial DNA (cox1 and 12S) to reconstruct the first phylogeny of Myzomorphus and, in combination with morphological data, assess the taxonomic limits between M. scutellatus and M. quadripunctatus. Our phylogenetic results confirm the monophyly of Myzomorphus and reveal a close relationship among M. birai, M. quadripunctatus and M. scutellatus. Using pairwise distance estimations, we found that the intraspecific variation of M. quadripunctatus is remarkably high (K2P: 0–11.7%; p-distances: 0–9.7%) and the interspecific distances of M. quadripunctatus in relation to M. birai and M. scutellatus (K2P: 14.8–20.1%; p-distances: 12–15%) are close to the intraspecific distances of M. quadripunctatus. We further analyzed the diagnostic characters of these species and found that their morphological intraspecific variations largely overlap. Altogether, our results demonstrate that the variability of M. birai, M. scutellatus and M. quadripunctatus represent polymorphisms of a single species. We thus argue for the synonymy of M. birai and M. scutellatus under M. quadripunctatus (syn. nov.) and highlight the need for multiple lines of evidence to solve the taxonomic problems in polymorphic species of Cerambycidae.